A ciência da docência : discurso epistemológico em tempo de cultura digital - Teixeira, Augusto Niche (2016)
The present doctoral thesis deals with teaching as a process of scientificity, teaching as a science. The work "the science of teaching: epistemological discourse in time of digital culture" reveals the necessary production of meaning and meaning for the production of scientificity and well-being in teaching in time of Digital Culture through reflection and re-signification of experiences Significant pedagogies. The study focused on the reality of undergraduate - Pedagogy Degree - whose subjects, teachers and students, reported and discussed the process of teaching academic-curricular knowledge and learning with the attribution of meaning and meaning, in time of Digital Culture and Technology perspective. The methodological construct of a qualitative nature and epistemological typology based on the filters and principles of complex, dialogic, recursive and hologramatic thinking resulted in a data collection and, therefore, in the digital analysis based and systematized through the NVivo11 qualitative data analysis software. Data were collected from closed questionnaires and semi-structured interviews. The research results point to the development of epistemologies for the attribution of meaning to knowledge constructed by professors and students at the undergraduate level, in the midst of the educational complexity of the third millennium in time of Digital Culture, through continuing education processes, taking Permanent education as a source and bridge for the constitution of teaching as science, the teaching act as recursive and hologramatic scientificity. In order to systematize the proposal in focus, 7 (seven) recursive phases for teacher training were presented, which, a priori, from a system of authors and theories, theoretical-practical constructs from action-reflection and the sharing of pedagogical knowledge, Result in teaching as scientific production and, consequently, in the teacher identity constitution in teaching as science. The proposition of an open model of continuous formation is justified by the need for teachers to be reflective and protagonists of the action-reflection-action movement about the exercise of teaching, thus being thinkers and scientists, (re)inventors and significant, from the act of educating.